Melatonin Engineered Adipose-Derived Biomimetic Nanovesicles Regulate Mitochondrial Functions and Promote Myocardial Repair in Myocardial Infarction - Zhang, Yang; Yang, Ning; Huang, Xu; Zhu, Yan; Gao, Shan; Liu, Zhongyang; Cao, Feng; Wang, Yabin (Frontiers in Cardiovascular Medicine, 2022)
Myocardial infarction (MI), one type of ischemic heart diseases, is the major reason for disability and mortality worldwide. Currently, extracellular vesicles (EVs) derived from adipose derived stem cell (ADSC) have been proven to be a potentially promising therapeutic treatment for MI. However, the inconvenience of isolation, the low productivity, and high cost of extracellular vesicles greatly limit their application in clinic. In this study, we constructed novel biomimic ADSC-derived nanovesicles (ADSC NVs) to achieve cell-free therapy for MI. Here, we firstly developed a novel Mel@NVs delivery system consisted of engineered ADSC NVs with melatonin (Mel). Then, the characterization and properties of Mel@NVs were performed. And the effect of Mel@NVs on cellular oxidative stress and myocardial infarction repair were conducted. The results showed that Mel@NVs treatment under ischemia mimic condition reduced cell apoptosis from 42.59%±2.69% to 13.88%±1.77%. Moreover, this novel engineered Mel@NVs could ameliorate excessive ROS generation, promote microvessel formation, and attenuate cardiac fibrosis, which further alleviate mitochondrial dysfunction and finally enhance myocardial repair. Hence, the engineered NVs show a potential strategy for MI therapy.